Efektivitas Edukasi Berbasis Leaflet dalam Meningkatkan Pengetahuan tentang Pemeriksaan Payudara Sendiri (Sadari) pada di SMA Negeri 1 Baitussalam - Salamah, Salamah; Aiman, Ummu; Fazlaini, Risna; Zaitun, Zaitun; Batubara, Apriany Ramadhan (Public Health Journal, 2026)
Breast cancer is one of the major health problems affecting women, including adolescents. Early detection can be performed through Breast Self-Examination (BSE); however, the level of knowledge regarding BSE among adolescent girls remains relatively low. This study aimed to determine the effect of  leaflet-based educational media on improving students' knowledge of BSE at SMA Negeri 1 Baitussalam, Aceh Besar. This study employed a quasi-experimental design using a one-group pre-test and post-test approach. The population consisted of all female students at SMA Negeri 1 Baitussalam, with a sample of 61 participants selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using the Wilcoxon Signed Ranks Test. The results showed that prior to the educational intervention, 37 respondents (60.7%) had a moderate level of knowledge, 15 respondents (24.6%) had good knowledge, and 9 respondents (14.7%) had poor knowledge regarding BSE. Following the  leaflet-based educational intervention, respondents' knowledge increased significantly, with 57 respondents (93.4%) demonstrating good knowledge and 4 respondents (6.6%) demonstrating moderate knowledge. No respondents remained in the poor knowledge category. The Wilcoxon Signed Ranks Test indicated a statistically significant difference between pre-test and post-test scores (p-value = 0.000). These findings demonstrate that  leaflet-based educational media is effective in improving female students' knowledge of BSE. In conclusion,  leaflets can serve as an accessible, cost-effective, and practical health education tool to enhance awareness of early breast cancer detection. It is recommended that healthcare professionals and schools utilize  leaflets more frequently in adolescent health education programs and provide continuous guidance to encourage adolescents to perform BSE regularly